Review on Energy Stored in Solar Cells and Converted to Operate Laboratory Apparatus - Dr. Nagham Mahmood Aljamali,; Mohammed Nawfal Abdul Maged Alkhafaji, (Journal of Power Electronics and Devices, 2021)
Researchers are actively working on developing technical solutions to store surplus energy for use during the night or on cloudy days, but most of the technologies that have been promoted to date have not succeeded in overcoming this obstacle. Despite the increasing reliance on renewable energies during the past few decades, especially solar energy, the dilemma of its irregularity and its continuity throughout the day or throughout the year represents an obstacle to it to seriously compete with fossil sources of energy. In the not too distant future, roofs, walls, windows, car bodies, clothing, and perhaps even skin, may be able to convert sunlight into usable energy. This will be thanks to the important developments currently taking place in the manufacture of solar panels, which give them some important characteristics to achieve this such as light weight, flexibility, transparency and thin thickness, which leads some experts to believe that solar energy will dominate the world thanks to its ease of access and scalability in a way that cannot be matched by any other source of energy. The researcher’s efforts are focused on further enhancing the energy production of solar energy systems by improving the efficiency of the solar cell, but the energy generated by the panels can also be increased in different ways. According to the study the researchers note that bifacial solar panels produce more energy per unit area than their counterparts, and that they can be exploited in places such as rooftops. This type of solar panel, along with tracking technology that captures more light, can significantly improve solar energy production from cells even without upgrading the cells capabilities.